1998
DOI: 10.2307/40285787
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Rhythm Perception as a Result of Unilateral Assimilation in Time-Shrinking

Abstract: In previous studies, we established an illusion of time perception that we called time-shrinking: an empty time interval, immediately preceded by a slightly shorter time interval, is underestimated. In the first experiment of the present study, we examined the perceived duration not only of the second interval (t2), but also of the first interval (tl). The empty time intervals tl and t2, making a total duration of 90,180, 360, or 720 ms, were presented such that the time ratio between them changed systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…We demonstrated that ERP components related to temporal perception could be extracted by contrasting the brain activations in the judgment condition and in the no-judgment condition. Behavioral results showed a clear assimilation: participants judged the two neighboring time intervals as equal when -40 ≤ (T1-T2) ≤ +40 ms. One of our previous studies has confirmed that the range of temporal assimilation was clearly beyond the range indicated by the just noticeable differences (JNDs) of short time intervals (Sasaki et al, 1998). These data agree with the present behavioral data, in which the 'same' responses in a certain range around zero millisecond should have been caused by assimilation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We demonstrated that ERP components related to temporal perception could be extracted by contrasting the brain activations in the judgment condition and in the no-judgment condition. Behavioral results showed a clear assimilation: participants judged the two neighboring time intervals as equal when -40 ≤ (T1-T2) ≤ +40 ms. One of our previous studies has confirmed that the range of temporal assimilation was clearly beyond the range indicated by the just noticeable differences (JNDs) of short time intervals (Sasaki et al, 1998). These data agree with the present behavioral data, in which the 'same' responses in a certain range around zero millisecond should have been caused by assimilation.…”
Section: Discussionsupporting
confidence: 82%
“…Following these findings, the above attenuation of the SNCt activity can be explained by the economic information processing in the brain. The attenuation of SNCt observed in Experiment 2 in conditions where neighboring time intervals are mostly perceived as equal seems to have been caused by the occurrence of the unilateral or bilateral assimilation (Sasaki et al, 1998;Miyauchi & Nakajima, 2005;2007;Nakajima, et al, 2004;ten Hoopen et al, 2006). According to our psychophysical model of unilateral temporal assimilation (Nakajima, et al, 2004), the perceived difference between T1 and T2 should be reduced by cutting the processing time for T2 after the offset of the 3rd marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They assured that time-shrinking, as assimilation, was asymmetric in time and unilateral, because the illusion appeared only when t2 was longer than t1, and only the perception of t2 was affected. Sasaki et al (1998) measured the PSEs of two neighboring empty time intervals and confirmed the idea that time-shrinking was unilateral assimilation. A closer look at their data shows that a different assimilation also seems to have appeared outside of the range in which the unilateral assimilation took place.…”
mentioning
confidence: 61%
“…It is often thought that these assimilations take place when a single continuous dimension is mapped into perceptual categories (e.g., rhythmic and phonemic categories) and does not occur directly with regard to the dimension constituting the stimulus pattern. A study of time perception (Sasaki, Nakajima, & ten Hoopen, 1998), however, suggested that assimilation in points of subjective equality (PSEs) of duration appeared when two empty time intervals were adjacent. This may indicate that assimilation takes place in the dimension of time itself.…”
mentioning
confidence: 98%